Edukasi Pijat Bayi untuk Stimulasi Tumbuh Kembang Anak di Puskesmas Putri Ayu Kota Jambi - Armina, Armina; Julaecha, Julaecha; Nurfitriani, Nurfitriani (Universitas Baiturrahim, 2025)
Infant massage is a touch therapy that can fulfill physical-biological, emotional and stimulation needs. The results of the preliminary study were known at the Putri Ayu Health Center, 2 mothers complained that their babies had not reached the ideal weight and did not know that baby massage could increase baby weight. The purpose of this community service is to provide education on baby massage to stimulate baby growth and development. The implementation of this community service was carried out in March-August 2023 at the Putri Ayu Health Center, Jambi City, targeting mothers with a total of 15 mothers with lecture and demonstration methods of baby massage. However, there were 12 mothers who could fill out the pre-test questionnaire and 9 mothers who completed it. The PKM implementation began with a 14-question pre-test of baby massage knowledge, then continued with the provision of leaflets and then continued with counseling starting from the material on the definition of baby massage, the benefits of baby massage, the timing of baby massage, the requirements for baby massage, baby massage members and baby massage techniques. Then followed by a demonstration of baby massage, oral evaluation of counseling material, attitudes and expectations of mothers regarding baby massage. The results of the pre-test community service were 58.33% with high knowledge, while the results of the post-test knowledge of mothers increased to 66.67% by being able to mention the definition of baby massage, the benefits of baby massage, the time to do baby massage, the conditions for implementing baby massage, and baby massage limbs. The success of baby massage education can improve mothers' knowledge and skills. The results of this community service are expected to be continued in the form of baby massage training for mothers.